Left Ventricular Twist Mechanics Before and After Aortic Valve Replacement: A Feasibility Study and Exploratory Analysis. (September 2022) - Zhang, Kan; Kumar, Nikhil; Alfirevic, Andrej; Sale, Shiva; You, Jing; Bauer, Andrew; Duncan, Andra E.
Introduction. We examined whether intraoperative assessment of left ventricular (LV) twist mechanics is feasible with transesophageal echocardiography (TEE). We then explored whether twist mechanics were altered by hemodynamic conditions or patient comorbidities. Methods. In this sub-analysis of clinical trial data, transgastric short-axis echocardiographic images of the LV base and apex were collected in patients having aortic valve replacement (AVR) at baseline and end of surgery. Transvalvular gradients and LV systolic and diastolic function were assessed using two-dimensional (2D) and Doppler echocardiography. 2D speckle-tracking echocardiography was used for off-line analysis of LV twist, twisting rate, and untwisting rate. We examined the intraoperative change in twist mechanics before and after AVR. LV twist mechanics were also explored by diabetic status, need for coronary artery bypass grafting (CABG), and use of epinephrine/norepinephrine. Results. Of 40 patients, 16 patients had acceptable TEE images for off-line LV twist analysis. Baseline median [Q1, Q3] LV twist was 12 [7, 16]°, twisting rate was 72 [41, 97]°/sec, and untwisting rate was −91 [−154, −56]°/s. Median [Q1, Q3] change in LV twist at end of surgery was −2 [−5, 3]°, twisting rate was 7 [−33, 31]°/s, and untwisting rate was 0 [−11, 43]°/s. No difference was noted between diabetic and non-diabetic patients or AVR and AVR-CABG patients. Conclusion. LV twist was augmented in patients with aortic stenosis, though twist indices were not affected by reduced afterload, diabetes, or coronary artery disease. Intraoperative assessment of twist mechanics may provide unique information on LV systolic and diastolic function, though fewer than 50% of TEE examinations successfully assessed twist. Clinical Trial Registry. This work is a sub-analysis of a clinical trial, registered on ClinicalTrials.gov on August 19, 2010 (NCT01187329), Andra Duncan, Principal Investigator.